The cat ate my gymsuit - Danziger, Paula, 1944-2004 (Putnam, 1998)
When the unconventional English teacher who helped her conquer many of her feelings of insecurity is fired, a junior high student uses her new found courage to campaign for the teacher's reinstatement.